Patient survival and tumor characteristics associated with CHEK2:p.I157T – findings from the Breast Cancer Association Consortium. Issue 1 (December 2016) - Muranen, Taru; Blomqvist, Carl; Dörk, Thilo; Jakubowska, Anna; Heikkilä, Päivi; Fagerholm, Rainer; Greco, Dario; Aittomäki, Kristiina; Bojesen, Stig; Shah, Mitul; Dunning, Alison; Rhenius, Valerie; et al.
Abstract Background P.I157T is aCHEK2 missense mutation associated with a modest increase in breast cancer risk. Previously, anotherCHEK2 mutation, the protein truncating c.1100delC has been associated with poor prognosis of breast cancer patients. Here, we have investigated patient survival and characteristics of breast tumors of germ line p.I157T carriers. Methods We included in the analyses 26, 801 European female breast cancer patients from 15 studies participating in the Breast Cancer Association Consortium. We analyzed the association between p.I157T and the clinico-pathological breast cancer characteristics by comparing the p.I157T carrier tumors to non-carrier and c.1100delC carrier tumors. Similarly, we investigated the p.I157T associated risk of early death, breast cancer-associated death, distant metastasis, locoregional relapse and second breast cancer using Cox proportional hazards models. Additionally, we explored the p.I157T-associated genomic gene expression profile using data from breast tumors of 183 Finnish female breast cancer patients (ten p.I157T carriers) (GEO: GSE24450). Differential gene expression analysis was performed using a moderatedt test. Functional enrichment was investigated using the DAVID functional annotation tool and gene set enrichment analysis (GSEA). The tumors were classified into molecular subtypes according to the St Gallen 2013 criteria and the PAM50 gene expression signature. Results P.I157T was not associated with increased risk of early death, breast cancer-associated death or distant metastasis relapse, and there was a significant difference in prognosis associated with the twoCHEK2 mutations, p.I157T and c.1100delC. Furthermore, p.I157T was associated with lobular histological type and clinico-pathological markers of good prognosis, such as ER and PR expression, low TP53 expression and low grade. Gene expression analysis suggested luminal A to be the most common subtype for p.I157T carriers and CDH1 (cadherin 1) target genes to be significantly enriched among genes, whose expression differed between p.I157T and non-carrier tumors. Conclusions Our analyses suggest that there are fundamental differences in breast tumors ofCHEK2 :p.I157T and c.1100delC carriers. The poor prognosis associated with c.1100delC cannot be generalized to otherCHEK2 mutations.